SCIENCE AS A MEANS TO THE DEVELOPMENT OF PSYCHOLOGY - Ana Estévez (Papeles del psicólogo, 2020)
Psychology has evolved from its definition as a treatise on the soul to the present day, where it is considered a science that studies the mind and human behavior. The path of moving away from philosophy and towards science has been complex because science was better suited to other disciplines where causality can be evaluated more easily than in psychology. In spite of the complexity of the object of analysis, psychology has contributed knowledge that has improved people’s lives in very diverse areas. Similarly, the approach toward science has provided psychology with systematic methods with which to organize its knowledge. This article aims to delve into the strengths that psychology has as a legitimate science. It also points out that the desire to learn and the scientific attitude as a critical attitude could be the way to improve psychology.